Comunicación organizacional y su impacto en el desarrollo económico en la ciudad de Quevedo año 2020 - Ortega Cevallos, Jaidy Lisseth (2021)
This research seeks to know how organizational communication has impacted economic development in the city of Quevedo, analyzing the change in business policies where corporate communication has been included as a strategy and the results it has had in the entities that have established it. For the development of the case study it was necessary to apply the types of field research, bibliographic from which data was obtained to select them, together with descriptive, deductive, statistical analytical methods that showed that good communication is much more than an exchange of data Since these allow integration, cooperation towards a single goal, which is the success of societies, considering the contributions that a good flow of information has internally and externally, it is proposed that entities are willing to a constant training that allows you to improve your skills and integration with your collaborators, motivating them to work as a team so that they fulfill each one with the assigned functions efficiently, optimizing the productivity of the goods and services offered to the consumer.